(3QSGdI ajeG jMJGL Edjg GdQLGd hGdfSGA (B((3aj GdHGg(B)s - (3GdJjaGTj , CMeO Hf jhSa Hf CMeO Hf CHj HcQ Hf MeOhf GdbjSj, TQa GdOjf,J (B651 (3g` s
(3ChdgG (B:s
(3hHYO abO bGd GdYdGeI GdJjaGTj QMeg Gddg JYGdi(B: (3gPG eG jMJGL Edjg GdfSGA hcPG GdQLGd , aj ESJYeGd GdHGg, hjfaY , hQJHJg Ydi ebOeI hYTQI CHhGH hNGJeI s
(3BNQgG (B:s
(3hjKHJ Ydjg GdOgf Ke jYGhOg cPdc eQGQkG aEfg dGjYhO TYQ CHOkG aGYde Pdc, hGddg jJhdi gOGc hGdSdGe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B273 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B208s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B13 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WH e (B24) s
Keywords: (3GdWHs